Black Votes Count : Political Empowerment in Mississippi After 1965 - Parker, Frank R. (Frank Rowley) (Book collections on Project MUSE., 1990)
A fascinating account by one of America's leading civil rights lawyers of the historic struggle for the right to vote. Frank Parker instructs how the battle for democracy has shifted from denial to dilution and persuasively argues for continued vigilance.